17β-Estradiol Attenuates Neuropathic Pain Caused by Spared Nerve Injury by Upregulating CIC-3 in the Dorsal Root Ganglion of Ovariectomized Rats - Xu, Zhen-Zhen; Chen, Qin-Yi; Deng, Shi-Yu; Zhang, Meng; Tan, Chao-Yang; Yang Wang,; Ma, Ke-Tao; Li, Li; Si, Jun-Qiang; Zhu, Li-Cang (Frontiers in Neuroscience, 2019)
Objective: The investigation aimed to investigate whether voltage-gated chloride channel-3 (ClC-3) played a role in the effects of 17β-estradiol (E2) on spared nerve injury (SNI)-induced neuropathic pain in ovariectomized (OVX) rats to elucidate the mechanisms of estrogen-mediated protection against neuropathic pain in castrated rats.Methods: Ovariectomized female Sprague–Dawley rats were divided into OVX, OVX+SNI, OVX+SNI+E2, OVX+SNI+E2+DMSO (vehicle, dimethylsulfoxide), or OVX+SNI+E2+Cltx (ClC-3-blocked Chlorotoxin) groups. Changes in ClC-3 protein expression in the L4-6 DRG were monitored by western blot. Behavioral testing used paw withdrawal threshold to acetone irritation and paw withdrawal thermal latency to thermal stimulation. Immunofluorescence was used to observe the localization and protein expression levels of ClC-3 in dorsal root ganglion (DRG) neurons of ovariectomized rats. OVX+SNI+E2 rats were subcutaneously injected with 17β-estradiol once daily for 7 d; a sheathed tube was implanted, and chlorotoxin was injected for 4 days. ClC-3 protein expression in each group was detected by western blot. ClC-3 mRNA expression was detected by quantitative real-time polymerase chain reaction. Patch clamp technology in current clamp mode was used to measure the current threshold (rheobase) DRG neurons and the minimal current that evoked action potentials as excitability parameters. The mean number of action potentials at double-strength rheobase (2 × rheobase) verified neuronal excitability.Results: Compared with OVX rats, OVX rats with SNI that were administered estradiol showed a lower paw withdrawal threshold to the acetone stimulus (P<0.01), indicating increased sensitivity to cold but not thermal pain. Co-immunofluorescent data revealed that ClC-3 was mainly distributed in A- and C-type nociceptive neurons. 17β-estradiol administration was associated with increased expression of ClC-3 (P<0.01). The lowest expression of ClC-3 protein following SNI in OVX rats was on day 7 in the DRG. 17β-estradiol-induced increase in ClC-3 expression was blocked by co-administration of Cltx (P<0.01). Patch clamp results suggested that estrogen attenuated the excitability of neurons induced by SNI by up-regulating the expression of ClC-3 in the dorsal root ganglia of ovariectomized rats (P<0.01). Conclusion: 17β-estradiol administration significantly improved cold allodynia thresholds in ovariectomized rats with SNI. The mechanism for this decreased sensitivity may be related to the upregulation of ClC-3 expression in the DRG.